2020
DOI: 10.1021/acs.macromol.9b02627
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Bonding as a Tool to Control Chain Structure of PEDOT: Electrochemical Synthesis in the Presence of Different Electrolytes

Abstract: The current knowledge about the presence of cation radicals in organic semiconductors is connected with oxidized constitutional units and their interaction with counterions. In this work, we have shown that the formation of cation radicals in poly­(3,4-ethylene­dioxythiophene) is induced by intermolecular electrostatic interactions, particularly by hydrogen-bond formation between formic acid and polymer. Raman, XPS, UV–vis, and EPR spectroscopies were used to prove that by using the simplest carboxylic acid, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…That fact was confirmed by high‐resolution X‐ray photoelectron spectroscopy (XPS) by the detailed investigation of the valent electron shell of sulfur in thiophene ring, where two peaks were observed, which correspond to the presence of sulfur in two oxidations states. [ 12 ]…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…That fact was confirmed by high‐resolution X‐ray photoelectron spectroscopy (XPS) by the detailed investigation of the valent electron shell of sulfur in thiophene ring, where two peaks were observed, which correspond to the presence of sulfur in two oxidations states. [ 12 ]…”
Section: Resultsmentioning
confidence: 99%
“…Previously it has been proved by us the chemical structure of PEDOT studied by the Raman spectroscopy and XPS and it was shown that PEDOT polymerized in the presence of formic acid is in a reduce state, and there is no oxidized sequence. [ 12 ] On the other hand, it was shown that hydrogen bonds between formic molecules and polymer chains induced the formation of cation radicals and therefore partially oxidized sulfur in thiophene (from XPS spectra it was estimated to be 27%). [ 12 ] Also, it was shown that orthophosphoric acid could interact with PEDOT chains with the formation of delocalized cation radicals.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 7 ] Detection of the cation radicals in the final powder could be explained by the presence of acid (formic acid), which is able to induce electrostatic interactions (hydrogen bonding formation), as recently shown by us. [ 31 ]…”
Section: Resultsmentioning
confidence: 99%
“…We know that formic acid can interact with PEDOT by hydrogen bonding. [ 31 ] Such interactions can induce electron‐charge transfer from thiophene sulfur to hydrogen in formic acid, accompanied by the formation of cation radicals. This interaction observed in the EPR signal of the final PEDOT powder (Figure 3c).…”
Section: Resultsmentioning
confidence: 99%